The cystic fibrosis airway milieu enhances rescue of F508del in a pre-clinical model. Issue 6 (20th December 2018) - Gentzsch, Martina; Cholon, Deborah M.; Quinney, Nancy L.; Boyles, Susan E.; Martino, Mary E.B.; Ribeiro, Carla M.P.
Cystic fibrosis is a life-shortening genetic disease with autosomal recessive inheritance. Most cystic fibrosis morbidity and mortality is associated with pulmonary disease. The cystic fibrosis transmembrane conductance regulator (CFTR) gene, which codes for a chloride channel required for proper hydration of airway epithelial surfaces, is mutated in cystic fibrosis, resulting in airway dehydration. As a result, cystic fibrosis patients suffer from chronic airway infection, inflammation and overproduction of mucus, which leads to airway obstruction. During the last decade, basic and clinical research has led to strategies for targeted therapies to successfully restore CFTR function in cystic fibrosis patients. The CF airway inflammatory milieu has a major impact on the efficacy of CFTR modulators, indicating that pre-clinical evaluation under conditions that mimic native inflamed CF airways is critical for optimising therapies. http://ow.ly/VrD130m770X